On-machine surface measurement and applications for ultra-precision machining: a state-of-the-art review - Li, Duo; Wang, Bo; Tong, Zhen; Blunt, Liam; Jiang, Xiangqian (International journal of advanced manufacturing technology, 2019)
Surface measurement is essential to enhance accuracy and efficiency in ultra-precision machining. In order to increase the measurement availability and efficiency, offline lab-based solutions are shifting towards the use of surface metrology upon manufacturing platforms. With the lack of remounting errors, on-machine surface measurement (OMSM) allows the deterministic assessment of manufactured surfaces just-in-time and also provides valuable feedback to the process control of ultra-precision machining. This paper is aimed at reviewing the state-of-the-art OMSM and applications in the ultra-precision machining process. The benefits and considerations on the integration of metrology are discussed. The merits and limitations among different OMSM types are compared as well. Finally, the challenges and outlook of the ultra-precision machining-metrology integration are highlighted.